Limitation of State Control Rights over Natural Resources in Renewable Energy Management - Ningtias, Ayu Dian; Rochmawanto, Munif; Isnaini, Enik; Cahyani, Nurma (Universitas Islam Lamongan, 2024)
Abstract The concept of new energy management policy and renewable energy in maintaining national energy security through the first three properties, private property, namely ownership rights held by individuals or legal entities although it does not mean that it provides private ownership rights over certain natural resources but provides opportunities for individuals to manage natural resources to get certain benefits. Second, common property, namely ownership rights held by groups or can be referred to as